Modernization of Regional Social Policy: Trends and Prospects - Olga A. Hasbulatova (Социологическая наука и социальная практика, 2014)
The article analyzes the processes of modernization in education, public health and social protection aimed at development of human capital in the Russian regions. The author highlights the prospects of implementation of the regional social policy.